THE EFFECTIVENESS OF BLENDED LEARNING METHODS IN IMPROVING HIGH SCHOOL STUDENT LEARNING OUTCOMES - Mansori (Adisam Publisher, 2025)
The Blended Learning method that integrates face-to-face instruction with online components has been analyzed to evaluate its effectiveness in improving learning outcomes in Senior High School students. This literature study has been conducted through the collection and analysis of various relevant sources, including academic journals, articles, and previous studies related to the implementation and outcomes of the blended learning method. The analysis shows that Blended Learning allows for more flexible and accessible learning, and provides a more personalized approach to students. It gives students more control over the time, place, and pace of their learning. Factors such as the availability of online learning materials, increased interactivity between students and teachers, and collaboration between students are described as having a positive impact on learning motivation and understanding of the material. In line with that, this literature study also highlights the importance of the role of teachers in designing and implementing effective learning and the challenges that may be faced, including the need for adequate technology training for teachers and students. Further research is recommended to identify specific strategies in curriculum adjustment that can further optimize the learning process and to evaluate the long-term impact of this method on students' academic competence. Taking into account the various factors identified, this study confirms that Blended Learning can effectively improve the learning outcomes of Senior High School students when implemented with appropriate strategies and sufficient support.